Digital (Self)-Defence by The Example of The Children’s Rights Protection - R. V. Khisamova (Теоретическая и прикладная юриспруденция)
In relation to the sphere of legal protection the author considers two legal phenomena: “digital self-protection” and “digital protection of rights”. Relaying on examples of actions taken by parents in order to protect the children’s rights on Internet, the author comes to the conclusion that the digital methods of protecting the right that exist today in practice can be considered by modern jurisprudence as alternative ways to protect the right or form a new legal institution of “digital self-protection”.